Shear resistance of multi-cell special-shaped CFST column to H-section steel beam joint. (July 2022) - Cheng, Yu; Yang, Yuanlong; Li, Binyang; Liu, Jiepeng; Yan, Wenxu; Frank Chen, Yohchia
Abstract: This paper studies the shear behavior of frame joint between multi-cell special-shaped concrete-filled steel tubular (CFST) column and H-section steel beam based on experimental research. The shear failure mode and hysteretic behavior of the joint were investigated from the experiment. A finite element (FE) model for multi-cell cruciform CFST column to H-section steel beam joint was conducted to study the influences of the following parameters on joint shear resistance: the axial compression ratio of column, aspect ratio of the joint, thickness of steel tube in joint panel zone, and the concrete compressive strength. Stress analysis on the steel tube and the concrete of each cell in joint panel zone was conducted by using the FE model to clarify the load transfer path and shear mechanism. Furthermore, a mechanical model for the joint shear resistance was developed, in which the contributions from the steel tube and concrete in different cells were considered. Based on the shear mechanical model, a calculation method for joint shear resistance is also proposed to facilitate the practical applications and verified by the experimental and numerical results.